Preparation, Characterization and Biological Activity Studies of Some Metal Complexes with New Schiff Base for Trimethoprim Ligand - Nazar Munem Abdalsahib (Journal of Global Pharma Technology, 2018)
A new ligand complexes have been synthesis from reaction of metal ions of MnII, CoII, NiII, CuII, ZnII, CdII and PdII with schiff base [(E)-1-((2-amino-5-(3, 4, 5-trimethoxybenzyl) pyrimidin-4-ylimino) methyl) naphthalen-2-ol [HL)]. The prepared [HL] was characterized by FT-IR, UV-Vis spectroscopy, 1H-13C-NMR spectra Mass spectra and melting point. The compounds were characterized by techniques UV-Vis and FT-IR spectral studies, micro analysis (C.H.N), determination of atomic absorption, chloride content, molar conductivity measurements, magnetic susceptibility and melting point. The ligand acts as a monobasic tridentate, coordinating through deprotonated phenolic O and azomethine N atoms. The compounds are neutral electrolytic in dimethylsulfoxide. The analytical and spectral data for these compounds indicated to (1:2) (metal: ligand) mole ratio. The metal content and magnetic moment suggest the square planar geometry for the palladium ion, but the other metal complexes show six-coordinate. Compounds were having been screened for their antimicrobial activities against various bacteria and fungi organisms using inhibition method.Keywords: Preparation, Characterization, Azomethine, Inhibition method.